Disruptive shave technology : considering the Dollar Shave Club model for a UK launch - O'Brien, Justin (Peter Justin) (London : SAGE Publications: SAGE Business Cases Originals, 2018)
This entrepreneurial marketing case outlines a subscription-based, low-cost shaving technology business opportunity -- the US-based Dollar Shave Club -- that two London-based entrepreneurs wanted to emulate for themselves in the UK. The case is introduced with a summary of the American business, which benefited from a highly successful but low-cost YouTube viral video that prominently featured its founder Michael Dubin. Superficially, the UK market does not appear to be attractive, according to summary Mintel consumer research and high-level competitor analysis. However, empathetic customer insight of dissatisfaction with ever-more important service convenience elements and over-branding from the dominant fast-moving consumer goods marketing leader were factors that ultimately ignited a paradigm shift in the marketing of male grooming. Students are invited to undertake a number of marketing analysis exercises before weighing a market entry recommendation for the two case protagonists, Zach and Dane.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Dollar Shave Club; Marketing -- Great Britain; Entrepreneurship -- Great Britain